Robot navigation for monitoring unsteady environmental boundaries without field gradient estimation. (December 2015) - Matveev, Alexey S.; Hoy, Michael Colin; Ovchinnikov, Kirill; Anisimov, Alexander; Savkin, Andrey V.
Abstract: A non-holonomic Dubins-car like robot should detect, locate, and track the boundary of an a priori unknown dynamic environmental scalar field. The field is measured by an on-board sensor in a point-wise fashion at the robot's location. The focus is on unsteady boundaries that arbitrarily evolve over time, and, e.g., may change shapes and sizes. We present a sliding mode control method for localizing and tracking such boundaries: the robot is steered to the boundary and circulates in its close proximity afterwards. The proposed control algorithm does not require estimation of the spatial gradient of the field and is non-demanding with respect to both computation and motion. Its mathematically rigorous justification is provided. The effectiveness of the proposed guidance law is confirmed by computer simulations and experiments with a real wheeled robot.